PEMANFAATAN PUPUK NPK TABLET UNTUKPENANAMAN GAHARU (Aquilaria spp) PADA TANAH ULTISOL - Oktapiana, .; Muin, Abdurrani; Fahrizal, . (Universitas Tanjungpura, 2017)
Agarwood planting in Pak Laheng village is done on ultisol soil which is known to be poor nutrient, so it needs to be given fertilizer and one of them is NPK tablet fertilizer. The objectives of the study were to examine the effect of NPK Tablet fertilizer on the growth of agarwood and to determine the appropriate dosage to be given to agarwood plants grown on Ultisol soil. The research was conducted at Pak Laheng Village, Toho District, until 12 week. Research methods was completely randomized design (CRD) with treatment: without fertilizer, NPK with 3 tablets/plant, 6 tablets /plant, and 9 tablet/plant. Each treatment was repeated in six replications. The data collected and analyzed is the increase of height (cm), diameter (mm), and the number of leaves. The results showed that NPK fertilizer tablet was influenced to the growth of agarwood plants until the age of 12 weeks. The dosage of fertilizer 9 tablets/plant are the best to accelerate plant growth on ultisol soil. Keywords: Ultisol Soil, NPK Tablets, and Aquilaria spp.